Unveiling gratitude in Javanese Muslim hajatan traditions: Cultural wisdom and social cohesion in the midst of modernization - Rizky Andana Pohan; M. Ramli; Adi Atmoko; Sa'dun Akbar; Fattah Hanurawan (Social Sciences and Humanities Open)
The hajatan tradition within the Javanese Muslim community is a culturally rich practice imbued with deep social and spiritual meaning, serving as a means to strengthen social bonds, preserve cultural values, and express gratitude to God, nature, and fellow human beings. While many studies have explored the role of cultural traditions in maintaining social stability and cultural identity, a significant gap remains in understanding how the hajatan tradition functions as a holistic mechanism for expressing gratitude amid rapid social changes. This research employs a qualitative approach with a participatory ethnographic design conducted over seven months in Kelurahan Mulyorejo, Kecamatan Sukun, Kota Malang. Data were collected through participant observation, in-depth interviews with community members, and analysis of related documents. The data were analyzed thematically using an inductive approach to identify patterns of gratitude within the hajatan tradition and its role in strengthening social cohesion and maintaining cultural identity. The research finds that the hajatan tradition in the Javanese Muslim community serves not only as a religious ceremony but also as a mechanism for coping with uncertainty, fostering solidarity, and expressing gratitude that spans spiritual, ecological, and social dimensions. Gratitude to God, nature, and fellow human beings is expressed through various practices such as communal prayers, shared meals, and gotong royong (mutual cooperation), all of which contribute to the psychological and social well-being of the community. These findings suggest that the hajatan tradition plays a critical role in maintaining social stability and the well-being of the Javanese Muslim community amid social change. This study enriches our understanding of the relevance and adaptability of cultural traditions in the modern world and offers new insights into how holistic gratitude can reinforce the cultural and spiritual identity of a community.